GTP-binding Protein-like Domain of AGAP1 Is Protein Binding Site That Allosterically Regulates ArfGAP Protein Catalytic Activity - Luo, Ruibai (American Society for Biochemistry and Molecular Biology, 2012)
AGAPs are a subtype of Arf GTPase-activating proteins (GAPs) with 11 members in humans. In addition to the Arf GAP domain, the proteins contain a G-protein-like domain (GLD) with homology to Ras superfamily proteins and a PH domain. AGAPs bind to clathrin adaptors, function in post Golgi membrane traffic, and have been implicated in glioblastoma. The regulation of AGAPs is largely unexplored. Other enzymes containing GTP binding domains are regulated by nucleotide binding. However, nucleotide binding to AGAPs has not been detected. Here, we found that neither nucleotides nor deleting the GLD of AGAP1 affected catalysis, which led us to hypothesize that the GLD is a protein binding site that regulates GAP activity. Two-hybrid screens identified RhoA, Rac1, and Cdc42 as potential binding partners. Coimmunoprecipitation confirmed that AGAP1 and AGAP2 can bind to RhoA. Binding was mediated by the C terminus of RhoA and was independent of nucleotide. RhoA and the C-terminal peptide from RhoA increased GAP activity specifically for the substrate Arf1. In contrast, a C-terminal peptide from Cdc42 neither bound nor activated AGAP1. Based on these results, we propose that AGAPs are allosterically regulated through protein binding to the GLD domain.